Dosing strategy of intrapleural bortezomib for myelomatous pleural effusion: A case report and review of literature - Yu‐Ming Li; Mei‐Hua Tsou; Tran‐Der Tan (eJHaem, 2024)
Abstract Myelomatous pleural effusion (MPE) is a rare, often treatment‐resistant complication of multiple myeloma. Intrapleural bortezomib shows promise but lacks standardized dosing. We report a 62‐year‐old woman with MPE treated with 1.3 mg/m2 (2 mg) subcutaneous and 0.975 mg/m2 (1.5 mg) intrapleural bortezomib on days 1 and 4. Despite MPE regression, significant toxicity occurred. Adjusted dosing to 0.65 mg/m2 (1 mg) for both routes on days 11 and 14 consolidated the response without side effects. This case demonstrates the feasibility of intrapleural therapy and the importance of cautious dosing. Literature supports equal intrapleural and systemic bortezomib dosing for MPE management.